Kinetic Study of Biogas Production from Animal Manure and Organic Waste in Semarang City by Using Anaerobic Digestion Method - Fahmi Arifan; Abdullah Abdullah; Siswo Sumardiono (Universitas Gadjah Mada, 2021)
The biogas fermentation from animal manure and organic waste was investigated with a comparison percentage of raw material used inside the digester with the anaerobic digestion process. Animal manure consists of cow dung and chicken manure, while organic waste consists of tofu liquid waste and cabbage waste. This study used a batch process that was operated at 55 °C incubator temperature for 90 days. The results of experimental data were predicted with a modified Gompertz model and first-order kinetic model. The equation of the modified Gompertz model to predict biogas production was with is cumulative production of methane; P∞ = methane production potential; Rm = maximum specific speed methane production; λ = is lag phase period or minimum time to produce biogas; e = math constant (2.7182) and t = biogas production cumulative time. The equation first-order kinetic model was Y = Ym (1-exp(-k). The highest biogas yield was obtained by variable 3 in both kinetic studies compared to 70% cow dung, 15% chicken manure, and 15% tofu liquid waste. Gompertz's kinetic study predicted variable three would produce 3273.20 mL/g of total solid (TS). In comparison, the first-order kinetic model predicted that variable three would produce 3517.95 mL/(g Ts).